2021
DOI: 10.1016/j.jad.2021.05.060
|View full text |Cite
|
Sign up to set email alerts
|

A living systematic review of the psychological problems in people suffering from COVID-19

Abstract: Objectives : We aimed to investigate the psychological problems on people infected with SARS-CoV-2 during the pandemic. Methods : In this living systematic review and meta-analyses, we searched seven electronic databases for cross-sectional studies and longitudinal studies on psychological problems on COVID-19 patients from Jan 1, 2020 to Oct 7, 2020. The primary outcome was prevalence of various psychological problems such as anxiety, depression, stress, insomnia, soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 72 publications
1
72
0
4
Order By: Relevance
“…Our findings are in line with the limited existing literature on both inpatients and outpatients, indicating a link between COVID-19 diagnosis and mental health status. 1 , 2 , 3 , 32 However, the longest follow-up in these studies was 6 months, except for one recent study with 1-year follow-up involving only patients admitted to hospital. In that study, 331 (26%) of 1271 patients with COVID-19 had anxiety or depression at 12-month follow-up, 32 which is similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in line with the limited existing literature on both inpatients and outpatients, indicating a link between COVID-19 diagnosis and mental health status. 1 , 2 , 3 , 32 However, the longest follow-up in these studies was 6 months, except for one recent study with 1-year follow-up involving only patients admitted to hospital. In that study, 331 (26%) of 1271 patients with COVID-19 had anxiety or depression at 12-month follow-up, 32 which is similar to the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse mental health symptoms 1 , 2 , 3 and comorbid psychiatric disorders 3 , 4 among patients with COVID-19 have been documented up to 6 months after hospital discharge. 3 , 5 , 6 Yet, in addition to the reported methodological shortcomings of the existing literature on this topic (ie, inpatient samples and absence of comparison groups), 5 , 7 little is still known about the long-term mental health of non-hospitalised patients with COVID-19 with varying illness severities.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health problems had been addressed from the results, as 17 respondents reported their mental health problems which was ranked as the most unhealthy condition among 341 respondents, details results in supplementary table 3. A recent living systematic review of the psychological disorders in people suffering from COVID-19 showed that a high proportion of COVID-19 patients manifested psychological problems such as anxiety, depression, post-traumatic stress disorder (PTSD), insomnia, somatization, and fear [60] . In addition to the patients with COVID-19, another study has shown that the epidemic has also caused adverse mental health consequences on the general population [61] .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introduction, more than forty years have passed since the publication of the original CES-D scale [ 12 ], and the CESD-R was undertaken to update the scale to reflect the DSM-IV text revision (TR) or DSM-5 classification [ 17 ]. This resulted in the creation of the CESD-R scale, consisting of 20 statements regarding well-being and behavior over the previous two weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The Center for Epidemiologic Studies Depression (CES-D) scale has been one of the most widespread scales for assessing depression since it was published in 1977; it was originally devised for screening and research in general population epidemiological studies and primary care [ 12 ]. However, more than forty years have passed since its publication, which necessitated the creation of the CES-D—Revised (CESD-R) scale.…”
Section: Introductionmentioning
confidence: 99%